Unraveling the complexity of PD-L1 assays: a descriptive review of the methodology, scoring, and practical implications - Vainer, Gilad W.; Badve, Sunil S.; Rajadurai, Pathmanathan; Soares, Fernando A.; Viale, Giuseppe; Büttner, Reinhard; Nuti, Shanthy; Juco, Jonathan; Krishnan, Radha; Tsao, Ming-Sound (Frontiers in Oncology, 2025)
PurposeOver the years, immune checkpoint inhibitors targeting the programmed cell death protein 1 (PD-1) and programmed cell death ligand 1 (PD-L1) axes have substantially improved clinical outcomes for patients with various types of cancer and stages. As a result, PD-L1 is the most recognized biomarker used to guide the selection of patients for treatment with anti–PD-(L)1 therapy. To date, there are 4 regulatory agency-approved and commercially available immunohistochemistry assays used to quantify PD-L1 tumor expression, with each assay approved for use with a specific PD-(L)1 inhibitor. In this descriptive review, we concisely summarize the methodology and scoring methods of each assay, as well as some of the challenges associated with real-world use of these assay systems.ResultsEach assay system is optimized for specific therapies, with its own anti-PD-L1 antibody, protocol, scoring, and interpretation guidelines. Although the methodologies of the 4 PD-L1 immunohistochemistry assay systems are similar, differences in their antibody clones, protocol conditions, instrumentation, and scoring methods limit assay interchangeability. The assays are also highly sensitive; slight deviations to the protocol can increase the risk of misclassifying the PD-(L)1 tumor status of patients. As a result, pathologists are faced with choosing which assay to perform with a limited tumor sample as well as with the challenges associated with the scoring methods and differences in regional regulatory approvals and infrastructure.ConclusionWhile the 4 approved PD-L1 immunohistochemistry assays provide clinical value, we offer pathologists suggestions to reduce the challenges associated with PD-L1 testing based on assay systems.